Двухфункциональный датчик давления-температуры на основе нитевидных кристаллов кремния - Druzhinin, A. A.; Kutrakov, A. P.; Liakh-Kaguy, N. S.; Vuitsyk, A. M. (PE "Politekhperiodika", Book and Journal Publishers, 2013)
The article presents the design of a pressure-temperature sensor based on p-type silicon whiskers, doped with boron, with a resistivity of 0,005 Ohm?cm. The sensor is operable in a temperature range from –100 to +200°C and at pressures from 0 to 20 MPa. The sensor is designed for a wide range of applications.